Multi-carrier information hiding algorithm based on three-dimensional model’s concave-convex structure characteristics - Shuai REN; Lei SHI; Binbin WANG; Huirong CHENG; Qianqian ZHANG; Honglin LIU (Dianxin kexue)
Aiming at the problem that the embedding capacity, invaibility and robustness of a single-carrier information hiding algorithm cannot be further improved due to the limitation of the number of carriers, the voxelization of the carrier and the embedding of secret information were combined with the concave-convex structure characteristics of the three-dimensional model, and a method was proposed.A multi-carrier information hiding algorithm based on the three-dimensional model’s concave-convex structure features.Firstly, the three-dimensional model was voxelized, and the three-dimensional model’s concave-convex structure features were extracted from the data set obtained after voxelization to classify the carrier library, and the concave-convex degree was obtained by conversion after the interval was encoded.Secondly, the secret information was segmented according to the number of carrier classifications and scrambled and optimized, so that the embedding of the carrier and the secret information was effectively connected through its classification and number of segments, and double embedding of secret information by encoding data of concavity intervals and voxelized coordinate points, respectively, to further improve the performance of the algorithm.Finally, the genetic algorithm was applied to optimize the secret information to complete the information hiding.The experiment shows that compared with the high-capacity three-dimensional model steganography algorithm based on a single carrier, the invisibility, robustness and capacity of the algorithm were significantly improved.